Usability Testing for an Open Educational Resource to Teach Language and Culture - Chang, Heejin; Windeatt, Scott (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2026)
This study focused on procedures for creating, testing, and developing a set of reusable online resources for use in English for academic purposes programmes. The aim of the materials was to help migrants and refugees develop the linguistic and cultural skills, knowledge, and understanding they would need to engage, interact, and collaborate effectively in a multicultural context. Development of the materials involved an iterative process using a three-stage approach:1. Expert review: Experts in relevant fields worked through the first version of the materials and providedcritical feedback, which guided initial revisions.2. Usability testing groups: Small groups of target users (students and teachers) used the revised materialsin workshop settings, and data were gathered from observations, interviews, and written comments.3. Wider evaluation: Larger-scale use and evaluation of the materials (which is ongoing, beyond the scopeof this paper).This article reports on the second stage.